Conductive paste, electronic component, and laminated ceramic capacitor
By using a mixed system of cellulose and polyvinyl acetals and anionic polymer compounds in the conductive paste, the problems of incompatibility of the adhesive resin combination in the conductive paste and insufficient dispersion of ceramic powder in the conductive paste are solved, and a conductive paste with high dispersion and high clingency is achieved, and a high capacity laminated ceramic capacitor requirements are met.
Patent Information
- Application Number
- CN202380067107.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-21
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the combination of the two organic binder resins in the conductive paste is usually incompatible, resulting in a significant reduction in function, and insufficient dispersion of the ceramic powder in the paste, and the density and smoothness of the dry film are insufficient to cope with the requirements of high-capacity laminated ceramic capacitors.
By introducing a mixed system of cellulose and polyvinyl acetals into the conductive paste, and forming polymer compounds through sulfur atom bonding, the compatibility and dispersion of the binder resin are improved, and anionic polymer compounds are used as dispersants to enhance the dispersion of the inorganic powder.
The excellent dispersion of the conductive powder and the high surface smoothness of the dry film are achieved, the clinging of the internal electrode layer and the film-film effect of the electrode pattern are improved, and the high capacity requirement of the laminated ceramic capacitor can be met.
Smart Images

Figure CN119894970A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste, an electronic component, and a multilayer ceramic capacitor. Background Art
[0002] As electronic devices such as mobile phones and digital devices become smaller and more powerful, electronic components including multilayer ceramic capacitors are also expected to be smaller and have higher capacitance. Multilayer ceramic capacitors have a structure in which multiple dielectric layers and multiple internal electrode layers are alternately stacked. By thinning these dielectric layers and internal electrode layers, miniaturization and higher capacitance can be achieved.
[0003] Multilayer ceramic capacitors are manufactured, for example, as follows. First, a conductive paste for internal electrodes is printed (applied) in a predetermined electrode pattern on the surface of a raw sheet containing a dielectric powder such as barium titanate (BaTiO3) and a binder resin such as a polybutyral resin, and dried to form a dry film. Next, a laminate is formed in which the dry film and the raw sheet are stacked in an alternating overlapping manner, heated and pressed to form an integrated state. The laminate is cut, and after being subjected to an organic binder removal treatment in an oxidizing atmosphere or an inactive atmosphere, it is fired to obtain a fired chip. Next, a slurry for external electrodes is applied to both ends of the fired chip, and after firing, the surface of the external electrode is plated with nickel, etc., to obtain a multilayer ceramic capacitor (MLCC).
[0004] In recent years, MLCC has been required to be further miniaturized and increased in capacity. For example, for internal electrodes using nickel, etc., research has been conducted on the thinning of dense and continuous electrode films. For ceramic dielectric materials and dielectric layers using them, research has been conducted on high dielectric constants and thin layers. Materials with dielectric layer thicknesses of 1.0 μm or less have also been put into practical use. Moreover, it is also expected that the electrode film will be less than 1.0 μm.
[0005] The required characteristics for miniaturization and high capacity of MLCC can be listed as suppressing the reduction of insulation resistance under high temperature and high voltage, that is, high reliability. The main reason for the reduction in insulation resistance is believed to be that the surface of the Ni electrode layer sandwiching the dielectric layer is uneven after the firing process, and the electric field is concentrated on the convex part. In the firing process, the Ni electrode layer is formed by sintering and densifying the Ni powder. However, the fine Ni powder is sintered quickly, so the electrode is interrupted and spheroidization is easy to occur. As a result, the effective electrode area of the Ni electrode layer is reduced, and the unevenness on the surface of the Ni electrode layer leads to a reduction in insulation resistance on the basis of the reduced capacity.
[0006] If the MLCC is thinned, the adhesion between the green sheet and the internal electrode layer will decrease, and problems such as curling and stacking deviation will occur frequently due to insufficient adhesion during stacking. Therefore, internal electrode slurry with plasticizers added is used. However, due to the plasticizer, the elastic modulus of the printed film decreases significantly, and it is easy to soften and deform. Therefore, even if the adhesion with the green sheet is improved, the disadvantages such as poor cutting of the internal electrode layer will become greater. In addition, due to the plasticizer, the amount of gas generated in the organic binder removal process increases, which becomes the cause of cracks.
[0007] When ceramic green sheets are stacked and pressed and bonded in the thickness direction, if the adhesion between the green sheets is weak, the bonding between the green sheets is poor. This poor bonding causes the occurrence of short circuit defects in multilayer ceramic capacitors, for example. In particular, from the perspective of the multilayer requirement of MLCC, it is necessary to use fine-grained dielectric powder to reduce the thickness of each dielectric layer. In addition, it is necessary to increase the number of stacking layers, so it is expected to improve this poor bonding. If the bonding between the green sheets is weak, structural defects such as delamination, voids, and cracks will occur during firing, reducing the yield of MLCC.
[0008] In order to improve such poor adhesion, the following measures 1) and 2) are conceivable.
[0009] 1) It is possible to increase the amount of binder or thickener in the conductive paste, but simply increasing their amounts does not improve the adhesion. On the contrary, when increasing their amounts, the amount of organic substances such as organic binder and thickener added to the conductive paste increases, and these organic substances become the cause of difficulty in removing the organic binder. Even if the organic binder is removed, the remaining organic substances (carbon residue) may sometimes cause structural defects in the subsequent firing process.
[0010] 2) When stacking a plurality of ceramic green sheets having a conductive paste film formed thereon, the surface of the coating film made of the conductive paste is smoothed, thereby increasing the contact area between the conductive paste film and the ceramic green sheets, and as a result, improving adhesion.
[0011] Although the purpose of improving the close contact between the internal electrode and the raw sheet is to prevent cracking, if butyral resin is used as the resin, it is possible to prevent the electrode from peeling off during cutting. So far, organic binders mainly use cellulose resins such as ethyl cellulose, but cellulose resins have high compatibility with various solvents and are effective in giving the conductive paste the rheological properties as the purpose, but on the other hand, they themselves are not very thermoplastic, so they have the disadvantage that the dry body part of the conductive paste and the raw sheet on the upper surface have almost no close contact during hot pressing. As a result, there has been no method to further improve the hot pressing properties of the internal electrodes of the raw sheet screen-printed with conductive paste and the raw sheet on the upper surface, prevent the stacking deviation of the electrodes inside the chip, improve the electrode alignment, and prevent the chip from cracking and peeling at the same time, so as to cope with the conductive paste for the internal electrodes of the multilayer ceramic capacitor with high stacking.
[0012] Therefore, the internal electrode paste may contain an organic resin, and the organic binder resin is preferably a mixed system of ethyl cellulose (EC) and polyvinyl butyral (PVB).
[0013] Ethyl cellulose (EC) has good solubility in solvents, printability, combustion decomposition, etc., and can therefore be used as a binder for internal electrode slurry. In addition, by using polyvinyl butyral (PVB) used in the green sheet as an organic binder resin, the adhesion strength between the green sheet and the dry film of the internal electrode slurry can be improved.
[0014] Patent Documents 1 and 2 disclose conductive pastes containing a cellulose resin and a polyvinyl butyral resin as a binder resin, and disclose that the adhesiveness with ceramic green sheets is improved.
[0015] Prior art literature
[0016] Patent Literature
[0017] Patent Document 1: Japanese Patent No. 5299904
[0018] Patent Document 2: Japanese Patent No. 5224722 Summary of the invention
[0019] Problems to be solved by the invention
[0020] However, generally speaking, when two different organic binder resins are mixed, they become an almost incompatible (non-compatible) combination. In the case of an incompatible combination of two organic binder resins, the two organic binder resins are basically not fused but exist independently, so not only can the expected performance not be exerted, but the functions are mostly significantly reduced.
[0021] In addition, if the resin is difficult to dissolve in the solvent, the smoothness of the slurry dried film deteriorates. For example, when EC and PVB are mixed, a typical "sea island structure" is observed, and phase separation is confirmed. As a result, the distribution of inorganic particles (conductive particles, ceramic powder) in the dry film is made uneven. In this way, the combination of organic materials in the slurry composition affects the dispersibility of inorganic particles (conductive particles, ceramic powder) in the dry film.
[0022] By making polymers that are originally immiscible compatible with each other, it is possible to combine the advantages of both, stabilize the interface between different polymers, and realize a uniform and stable dispersion state.
[0023] In addition, in the conductive paste disclosed in Patent Documents 1 and 2, since polyvinyl butyral resin is included, the adhesion between the dry film and the green sheet can be improved. However, in these technologies, since cellulose resin and polyvinyl butyral resin are used together, due to the poor compatibility of the two resins, sometimes the dispersion of conductive powder and ceramic powder in the conductive paste is insufficient, or the density and smoothness of the dry film of the conductive paste become insufficient. Such dry film characteristics cannot be said to be sufficient to cope with the high capacity of multilayer ceramic capacitors in recent years.
[0024] In view of such circumstances, an object of the present invention is to provide a conductive paste, an electronic component and a multilayer ceramic capacitor, wherein an internal electrode layer having a smooth dry film and excellent adhesion can be formed in a conductive paste using micronized conductive powder and ceramic powder for miniaturization and thinning of multilayer ceramic electronic components.
[0025] Means used to solve problems
[0026] In order to solve the above-mentioned problems, the conductive paste of the present invention comprises a conductive powder, a ceramic powder, a dispersant, a binder resin and an organic solvent, wherein the binder resin comprises cellulose, polyvinyl acetal, and a polymer compound in which a cellulose-based compound and a polyvinyl acetal-based compound are bonded via sulfur atoms, wherein the molar ratio of the sulfur atoms contained in the polymer compound to the total of the cellulose and the cellulose-based compound is 0.3 to 1.7, and the dispersant is an anionic polymer compound.
[0027] The dispersant may include a carboxyl group or a carboxylic anhydride group.
[0028] It is also possible that the cellulose-based compound is a cellulose derivative having a thiol group or a vinyl group, and the polyvinyl acetal-based compound is a polyvinyl acetal resin having a thiol group or a vinyl group. When the cellulose derivative has a thiol group, the polyvinyl acetal resin has a vinyl group that reacts with the thiol group, and when the cellulose derivative has a vinyl group, the polyvinyl acetal resin has a thiol group that reacts with the vinyl group.
[0029] The cellulose derivative may be ethyl cellulose having a thiol group or a vinyl group, and the polyvinyl acetal resin may be polyvinyl butyral having a thiol group or a vinyl group.
[0030] It may also be that the cellulose-based compound is a first esterification product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of cellulose, and the polyvinyl acetal-based compound is a second esterification product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of polyvinyl acetal, when the first esterification product has a thiol group, the second esterification product has a vinyl group, and when the first esterification product has a vinyl group, the second esterification product has a thiol group, and the polymer compound is a thiol-ene reaction product of the first esterification product and the second esterification product.
[0031] Alternatively, the first esterification product is a product formed by dehydration condensation of a carboxyl group of 3-allyloxypropionic acid and a hydroxyl group of ethyl cellulose, and the second esterification product is a product formed by dehydration condensation of a carboxyl group of 3-mercaptopropionic acid and a hydroxyl group of polyvinyl butyral.
[0032] Alternatively, the conductive powder may be nickel powder.
[0033] The number average particle size of the conductive powder may be 0.05 μm or more and 1.0 μm or less.
[0034] Alternatively, the ceramic powder may contain barium titanate.
[0035] The ceramic powder may have a number average particle size of 0.01 μm or more and 0.5 μm or less.
[0036] The content of the ceramic powder may be 1 mass % or more and 20 mass % or less.
[0037] The conductive paste of the present invention may be used for internal electrodes of multilayer ceramic components.
[0038] In order to solve the above-mentioned problems, the electronic component of the present invention is an electronic component formed using the conductive paste of the present invention.
[0039] In order to solve the above-mentioned problems, a multilayer ceramic capacitor of the present invention includes a laminated body including at least dielectric layers and internal electrode layers, wherein the internal electrode layers are formed using the conductive paste of the present invention.
[0040] Effects of the Invention
[0041] The conductive paste of the present invention has excellent dispersibility of conductive powder and high surface smoothness in the dried film after coating. In addition, the electrode pattern of electronic components such as multilayer ceramic capacitors formed using the conductive paste of the present invention also has excellent adhesion when forming thin-film electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 1 and 2 are a perspective view and a cross-sectional view showing a multilayer ceramic capacitor according to the present embodiment.
[0043] Figure 2 This is a diagram for evaluating the adhesion between a dry film obtained by printing and drying a conductive paste and a green sheet. DETAILED DESCRIPTION
[0044] Hereinafter, one embodiment of the conductive paste, electronic component, and multilayer ceramic capacitor of the present invention will be described.
[0045] [Conductive paste]
[0046] The conductive paste of the present embodiment includes conductive powder, ceramic powder, a dispersant, a binder resin, and an organic solvent. Hereinafter, each component will be described in detail.
[0047] (Conductive powder)
[0048] The conductive powder is not particularly limited, and metal powder can be used, for example, one or more powders selected from Ni, Pd, Pt, Au, Ag, Cu and their alloys can be used. Among them, from the viewpoints of conductivity, corrosion resistance and cost, Ni or its alloy powder is preferred. As a Ni alloy, for example, an alloy (Ni alloy) of Ni and at least one element selected from the group consisting of Mn, Cr, Co, Al, Fe, Cu, Zn, Ag, Au, Pt and Pd can be used. The content of Ni in the Ni alloy is, for example, 50% by mass or more, preferably 80% by mass or more. In addition, in order to suppress the rapid gas generation caused by partial thermal decomposition of the binder resin during the debonding process, the Ni powder can contain about hundreds of ppm of S.
[0049] The method for producing the conductive powder is not particularly limited, and examples thereof include a method of directly precipitating chloride vapor from a gas phase in hydrogen, an atomization method from molten metal, a spray pyrolysis method using an aqueous solution, a wet method of reducing a raw material metal salt in an aqueous solution, and the like.
[0050] The number average particle size of the conductive powder is not particularly limited, and can be selected according to the size of the electronic component of the object of use. The number average particle size of the conductive powder is preferably 0.5 μm or less, and more preferably 0.3 μm or less, for example, for use in multilayer ceramic capacitors that are being developed into thin films. When the average particle size is greater than 0.5 μm, the surface of the internal electrode sometimes becomes uneven, which deteriorates the electrical properties of the capacitor, so it is not preferred. In addition, the lower limit of the average particle size of the conductive powder is not particularly limited, for example, it is greater than 0.03 μm. When the number average particle size is less than 0.03 μm, handling becomes extremely difficult.
[0051] The number average particle size of the conductive powder is a value obtained by observation using a scanning electron microscope (SEM), and is an average value obtained by measuring the particle sizes of a plurality of particles one by one based on an image obtained by observation using the SEM at a magnification of 10,000 times.
[0052] The content of the conductive powder is preferably 30% by mass or more and less than 70% by mass, more preferably 40% by mass or more and 60% by mass or less, relative to the total amount of the conductive paste. When the content of the conductive powder is within the above range, the conductivity and dispersibility are excellent.
[0053] (Ceramic powder)
[0054] The ceramic powder is not particularly limited. For example, in the case of a conductive paste for internal electrodes of a multilayer ceramic capacitor, a known ceramic powder is appropriately selected according to the type of multilayer ceramic capacitor to be applied. The ceramic powder may be, for example, a perovskite oxide containing Ba and Ti, preferably barium titanate (BaTiO3).
[0055] As the ceramic powder, a ceramic powder containing barium titanate as a main component and oxide as a secondary component can also be used. As oxides, oxides of Mn, Cr, Si, Ca, Ba, Mg, V, W, Ta, Nb and one or more rare earth elements can be listed. In addition, as the ceramic powder, for example, a ceramic powder of a perovskite-type oxide ferroelectric in which the Ba atoms and Ti atoms of barium titanate (BaTiO3) are replaced by other atoms such as Sn, Pb, Zr, etc. can also be used.
[0056] In the conductive paste for the internal electrode, a powder having the same composition as the dielectric ceramic powder constituting the green sheet of the multilayer ceramic capacitor can also be used as the ceramic powder. This can suppress the generation of cracks caused by the mismatch of shrinkage at the interface between the dielectric layer and the internal electrode layer during the sintering process. As such ceramic powder, in addition to the above, for example, oxides such as ZnO, ferrite, PZT, BaO, Al2O3, Bi2O3, R (rare earth element) 2O3, TiO2, and Nd2O3 can be listed. In addition, one ceramic powder can be used, or two or more ceramic powders can be used.
[0057] The number average particle size of the ceramic powder is, for example, in the range of 0.01 μm to 0.5 μm, preferably in the range of 0.01 μm to 0.3 μm. By making the number average particle size of the ceramic powder in the above range, when used as an internal electrode slurry, a sufficiently fine and thin uniform internal electrode can be formed. The number average particle size is a value obtained by observation using a scanning electron microscope (SEM), and is an average value obtained by measuring the particle sizes of multiple particles one by one based on an image obtained by observation using an SEM at a magnification of 50,000 times.
[0058] The content of the ceramic powder is preferably 1 part by mass or more and 30 parts by mass or less, and more preferably 3 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the conductive powder. When the content of the conductive powder is within the above range, the conductivity and dispersibility are excellent.
[0059] The content of the ceramic powder is preferably 1% by mass or more and 20% by mass or less, and more preferably 5% by mass or more and 20% by mass or less, relative to the total amount of the conductive paste. When the content of the conductive powder is within the above range, the conductivity and dispersibility are excellent.
[0060] (Binder resin)
[0061] The binder resin used in the conductive paste of the present embodiment includes cellulose, polyvinyl acetal, and a polymer compound in which a cellulose compound and a polyvinyl acetal compound are bonded via sulfur atoms, wherein the molar ratio of the sulfur atoms contained in the polymer compound to the total of the cellulose and the cellulose compound is 0.3 to 1.7.
[0062] That is, the binder resin used in the conductive paste of the present embodiment includes a polymer compound formed by bonding a cellulose compound and a polyvinyl acetal compound. Moreover, the number average molecular weight (Mn) of the polymer compound is preferably 20,000 to 200,000 based on the standard polystyrene conversion value based on gel permeation chromatography (GPC). Moreover, the content of the polymer compound formed by bonding a cellulose compound and a polyvinyl acetal compound is preferably 1 part by mass or more and 10 parts by mass or less, and more preferably 1 part by mass or more and 8 parts by mass or less, relative to 100 parts by mass of the conductive powder.
[0063] The polymer compound of the present embodiment has a portion formed of a cellulose compound and a portion formed of a polyvinyl acetal compound, so the dry film obtained from the conductive paste of the present embodiment can have surface smoothness due to the cellulose compound and adhesion to the green sheet due to the polyvinyl acetal compound. Furthermore, the polymer compound can also solve the problem of poor dispersion of the conductive paste by having the structure of the incompatible cellulose compound and the polyvinyl acetal compound in the same molecule.
[0064] Here, even if the molar ratio of the sulfur atoms contained in the polymer compound to the total of the cellulose and the cellulose-based compound is 0.5 to 2, the surface roughness of the dry film is excellent compared to the conventional conductive paste using cellulose and polyvinyl acetal resin as binder resins, but if the molar ratio is 0.3 to 1.7, the surface roughness and dry film density of the dry film of the conductive paste are more excellent. The molar ratio of the sulfur atoms contained in the polymer compound to the total of the cellulose and the cellulose-based polymer compound is 0.3 to 1.7, and more preferably the molar ratio is 0.5 to 1.5.
[0065] The polymer compound in which a cellulose-based compound and a polyvinyl acetal-based compound are bonded and which can be used in the present embodiment will be described in more detail.
[0066] Both cellulose and polyvinyl acetal have hydroxyl groups in the molecule. Cellulose compounds and polyvinyl acetal compounds are prepared. The cellulose compounds have functional groups that can react with other compounds to form bonds in the hydroxyl groups of cellulose, and are chemically modified using reactive functional groups. On the other hand, the polyvinyl acetal compounds have functional groups that can react with other compounds to form bonds and are different from the functional groups introduced into the cellulose compounds in the hydroxyl groups of the polyvinyl acetal polymer compounds, and are chemically modified using reactive functional groups. That is, the reactive functional groups introduced into the cellulose compounds are different from the reactive functional groups introduced into the polyvinyl acetal compounds. In addition, the functional groups introduced into the cellulose compounds react with the functional groups introduced into the polyvinyl acetal compounds, but it is difficult to react between the same functional groups. Here, it is difficult to react between the same functional groups to avoid bonding between cellulose compounds and polyvinyl acetal compounds.
[0067] Moreover, if the functional group introduced into the cellulose compound is bonded with the functional group introduced into the polyvinyl acetal compound, a polymer compound bonded with the cellulose compound and the polyvinyl acetal compound can be obtained. Specifically, if a thiol group is introduced into cellulose to make a cellulose compound, and a vinyl group is introduced into a polyvinyl acetal resin to make a polyvinyl acetal compound, then the thiol group and the vinyl group are in the presence of a nucleophilic reagent and under the condition of generating free radicals, the double bond of the vinyl group is bonded to the sulfur atom of the thiol group. As a polymer compound of the binder resin used in the conductive paste of the present embodiment, a polymer compound bonded with the polyvinyl acetal compound can be obtained by utilizing the bonding reaction of the thiol group and the vinyl group. Of course, vinyl groups can also be introduced into the hydroxyl group of cellulose to make a cellulose compound, and thiol groups can be introduced into the hydroxyl group of the polyvinyl acetal resin to make a polyvinyl acetal compound.
[0068] That is, the cellulose-based compound may be a cellulose derivative having a thiol group or a vinyl group, and the polyvinyl acetal-based compound may be a polyvinyl acetal resin having a thiol group or a vinyl group. Furthermore, when the cellulose derivative has a thiol group, the polyvinyl acetal resin has a vinyl group that reacts with the thiol group, and when the cellulose derivative has a vinyl group, the polyvinyl acetal resin has a thiol group that reacts with the vinyl group.
[0069] The cellulose-based polymer compound used as the binder resin of the conductive paste of this embodiment is preferably a polymer compound in which the hydroxyl groups of cellulose, which is a natural polymer, are bonded to a compound and chemically modified. The chemical modification here is different from the chemical modification of introducing a reactive functional group as described above.
[0070] The bonding of the compound with the hydroxyl group of cellulose can be exemplified by alkyl etherification, esterification, etc. Examples of cellulose having a hydroxyl group include methyl cellulose, ethyl cellulose, propyl cellulose, butyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxybutyl methyl cellulose, cellulose acetate (acetyl cellulose, diacetyl cellulose, triacetyl cellulose, etc.), cellulose acetate propionate, cellulose acetate butyrate, nitrocellulose, etc. Cellulose may be used alone or in combination of two or more.
[0071] Since the conductive paste of the embodiment contains an organic solvent, it is preferred that cellulose also dissolves in the organic solvent. From the viewpoint of solubility in the organic solvent and smoothness of a dried film of the conductive paste, ethyl cellulose is more preferably used as the cellulose.
[0072] The molecular weight of cellulose affects the viscosity of the conductive paste of the present embodiment. The number average molecular weight (Mn) of cellulose is preferably 10,000 to 100,000, more preferably 10,000 to 80,000, in terms of standard polystyrene conversion value based on GPC.
[0073] When the number average molecular weight of cellulose is less than 10,000, the viscosity of the conductive paste becomes low, and when the number average molecular weight of cellulose is greater than 100,000, the viscosity of the conductive paste may become too high.
[0074] Not all hydroxyl groups of cellulose are chemically modified. The glucose ring that makes up cellulose has three hydroxyl groups, but if we average the number of hydroxyl groups per glucose ring of cellulose, 0.1 to 1 hydroxyl group remains as a hydroxyl group and is not chemically modified. In this way, reactive functional groups are introduced into the hydroxyl groups that have not been chemically modified.
[0075] On the other hand, polyvinyl acetal is generally a polymer composed of monomer units of vinyl acetal / vinyl alcohol / vinyl acetate, and can be obtained by saponifying polyvinyl acetate to form polyvinyl alcohol, and then acetalizing the polyvinyl alcohol. Specifically, polyvinyl acetal (polyvinyl butyral) obtained by butyralizing polyvinyl alcohol, polyvinyl acetal (polyvinyl formal) obtained by formalizing polyvinyl alcohol, etc. can be cited.
[0076] The polyvinyl acetal may be a commercially available product, and various polyvinyl acetals having different degrees of butyralization, formalization, acetyl group content, hydroxyl group content, molecular weight, etc. are sold by Sekisui Chemical Co., Ltd., Kuraray Co., Ltd., etc. The polyvinyl acetal may be used alone or in combination of two or more.
[0077] The polyvinyl acetal is preferably soluble in an organic solvent. From the viewpoint of high solubility in an organic solvent, the polyvinyl acetal is more preferably polyvinyl butyral.
[0078] Polyvinyl acetal affects film strength and solution viscosity according to its molecular weight. Therefore, the number average molecular weight of polyvinyl acetal is preferably in the range of 5,000 to 150,000, more preferably in the range of 10,000 to 100,000, in terms of standard polystyrene conversion value based on GPC.
[0079] When the number average molecular weight of polyvinyl acetal is less than 5,000, the solution viscosity becomes extremely low, and viscosity adjustment of the inorganic particle-containing composition (slurry or slurry) becomes difficult. In addition, there is a risk that the strength and adhesion of the film formed by applying and drying the inorganic particle-containing composition will be reduced.
[0080] Polyvinyl acetal has at least one hydroxyl group in one molecule. Generally, polyvinyl acetal has 20 to 40 mol% of hydroxyl groups as vinyl alcohol units constituting the polymer. Reactive functional groups are introduced into the hydroxyl groups for chemical modification.
[0081] As the compound that reacts with the hydroxyl group of cellulose to chemically modify it, a compound having a thiol group or a vinyl group at one end and a carboxyl group at the other end can be used. The carboxyl group of the compound forms an ester bond with the hydroxyl group of the cellulose polymer compound by dehydration condensation.
[0082] A method for synthesizing the polymer compound used in this embodiment will be described.
[0083] In order to obtain a cellulose-based compound or a polyvinyl acetal-based compound, a compound having the following functional groups, i.e., a functional group reactive with a hydroxyl group and a functional group reactive with other compounds, can be esterified or etherified with the hydroxyl group of cellulose or the hydroxyl group of polyvinyl acetal. Examples of the functional group reactive with a hydroxyl group include a carboxyl group and a hydroxyl group.
[0084] The esterification reaction can be carried out using a condensing agent, for example. Examples of the condensing agent include carbodiimide, diphenylphosphoryl azide, 1-hydroxybenzotriazole, and the like. The condensing agent can be used alone or in combination of two or more. Among them, carbodiimide is preferred because of its versatility and excellent reactivity, and can react under low temperature conditions without being affected by moisture in the reaction environment.
[0085] Examples of carbodiimide include dicyclohexylcarbodiimide, diisopropylcarbodiimide, N-[3-(dimethylamino)propyl]-N'-ethylcarbodiimide, and N-[3-(dimethylamino)propyl]-N'-ethylcarbodiimide methyl iodide. Among them, dicyclohexylcarbodiimide and diisopropylcarbodiimide are preferred from the viewpoint of availability. In addition, when using carbodiimide, it is also preferred to use dimethylaminopyridine or triethylamine as a base in a range of 0.01 mol% to 10 mol% relative to the carbodiimide as a reaction accelerator.
[0086] The etherification reaction can be efficiently carried out by using an alkali metal hydroxide such as KOH and NaOH; or an alkali metal hydride such as NaH and KH as a reaction catalyst.
[0087] In order to obtain a cellulose-based compound, it is also preferred to dissolve cellulose in an aprotic solvent such as ethyl acetate, mix a compound having a carboxyl group that is ester-bonded with a hydroxyl group and a vinyl or thiol group as a functional group that reacts with other compounds, and use a condensing agent and dimethylaminopyridine as a base such as a nucleophilic reagent for promoting the esterification reaction in an amount within a range of 0.01 mol % to 10 mol %.
[0088] The molar ratio of sulfur atoms in the polymer compound used in the present embodiment to the total of cellulose and cellulose-based compounds is 0.3 to 1.7. Therefore, 0.3 to 1.7 mol of a compound having a functional group reactive with other compounds needs to be added to 1 mol of cellulose.
[0089] The reaction temperature for synthesizing the cellulose-based compound is preferably in the range of room temperature to 50°C.
[0090] In the system where the synthesis reaction of the cellulose compound is completed, unreacted cellulose without the introduction of a hydroxyl group and a functional group reactive with other compounds, a cellulose compound introduced with one reactive functional group, and a cellulose compound introduced with multiple reactive functional groups are mixed. Chemical modification is a matter of probability, but the cellulose compound in which one hydroxyl group of cellulose is chemically modified is the most common. Then, after the synthesis of the cellulose compound is completed, the solvent can be removed by distillation.
[0091] In order to synthesize polyvinyl acetal compounds, it is also preferred to dissolve polyvinyl acetal in an aprotic solvent such as ethyl acetate, mix a compound having a carboxyl group that is ester-bonded with a hydroxyl group and a vinyl group or a thiol group as a functional group that reacts with other compounds, and use a condensing agent and dimethylaminopyridine as a base such as a nucleophilic reagent for promoting the esterification reaction in a range of 0.01 mol% to 10 mol%.
[0092] The reaction temperature for chemical modification of the hydroxyl group of polyvinyl acetal is preferably in the range of room temperature to 50° C. Then, after the synthesis of the polyvinyl acetal compound is completed, the solvent may be distilled off.
[0093] The polymer compound used in the present embodiment is prepared by dissolving a cellulose compound and a polyvinyl acetal compound in a solvent, adding a free radical generator and heating, thereby causing a vinyl group of one of the cellulose compound and the polyvinyl acetal compound to react with a thiol group of the other, thereby bonding the cellulose compound and the polyvinyl acetal compound.
[0094] Alternatively, the cellulose compound and the polyvinyl acetal compound may be dissolved in a solvent, and a nucleophilic reagent represented by a base such as amine may be added and heated.
[0095] The temperature of the reaction for bonding the cellulose compound and the polyvinyl acetal compound can be appropriately selected, but is preferably 60° C. or higher.
[0096] The solvent may be an acetate solvent such as dihydroterpineol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate, isobornyl isobutyrate, ethylene glycol monobutyl ether acetate, dipropylene glycol methyl ether acetate, or a terpene solvent such as terpineol and dihydroterpineol. If the solvent used in the conductive paste is used as the solvent, a carrier in which the obtained polymer compound is dissolved in the solvent may be prepared.
[0097] In this embodiment, in addition to the polymer compound formed by bonding a cellulose compound and a polyvinyl acetal compound, a cellulose resin such as methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, an acrylic resin, a butyral resin such as a polyvinyl acetal resin, etc. can be added. The molecular weight of the resin that can be added is about 20,000 to 200,000 in terms of GCP.
[0098] The content of the binder resin is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 6% by mass, relative to the total amount of the conductive paste. When the content of the binder resin is within the above range, the conductivity and dispersibility are excellent.
[0099] For example, the cellulose derivative may be ethyl cellulose having a thiol group or a vinyl group, and the polyvinyl acetal resin may be polyvinyl butyral having a thiol group or a vinyl group.
[0100] Specifically, the cellulose-based compound may be a first esterification product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of cellulose, and the polyvinyl acetal-based compound may be a second esterification product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of polyvinyl acetal. Furthermore, when the first esterification product has a thiol group, the second esterification product may have a vinyl group, and when the first esterification product has a vinyl group, the second esterification product may have a thiol group, and the polymer compound may be a thiol-ene reaction product of the first esterification product and the second esterification product.
[0101] More specifically, the first esterification product may be a product formed by dehydration condensation of the carboxyl group of 3-allyloxypropionic acid and the hydroxyl group of ethyl cellulose, and the second esterification product may be a product formed by dehydration condensation of the carboxyl group of 3-mercaptopropionic acid and the hydroxyl group of polyvinyl butyral.
[0102] (Organic Solvent)
[0103] The organic solvent is not particularly limited, and a known organic solvent that can dissolve the above-mentioned binder resin can be used. As the organic solvent, for example, acetate solvents such as dihydroterpineol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate and isobornyl isobutyrate, ethylene glycol monomethyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, and dipropylene glycol methyl ether acetate, terpene solvents such as terpineol and dihydroterpineol, hydrocarbon solvents such as tridecane, nonane, and cyclohexane, and petroleum hydrocarbon solvents such as mineral spirits can be cited. In addition, the organic solvent can be used alone or in combination.
[0104] The content of the organic solvent is preferably 40 parts by mass or more and 100 parts by mass or less, and more preferably 65 parts by mass or more and 95 parts by mass or less, based on 100 parts by mass of the conductive powder. When the content of the organic solvent is within the above range, the conductivity and dispersibility are excellent.
[0105] The content of the organic solvent is preferably 20% by mass or more and 60% by mass or less, and more preferably 35% by mass or more and 55% by mass or less, relative to the total amount of the conductive paste. When the content of the organic solvent is within the above range, the conductivity and dispersibility are excellent.
[0106] (Dispersant)
[0107] The conductive paste of this embodiment contains a polymer dispersant. The polymer dispersant acts to be adsorbed on the surface of the inorganic powder (conductive powder and ceramic powder) to suppress the aggregation of the inorganic powders, or to improve the wettability with the organic vehicle to disperse the inorganic powders in the conductive paste.
[0108] The polymer dispersant is anionic, preferably having a carboxyl group or a carboxylic anhydride group. By using anionic polymer dispersants, the dispersibility of inorganic powders such as conductive powders and ceramic powders in organic carriers can be further improved. Here, the carboxylic anhydride group refers to the state in which H2O is dehydrated from two carboxyl groups and anhydrous. For example, anhydrides such as phthalic anhydride and maleic anhydride can be cited, which are units of molecules composed of two carboxyl groups in a dehydrated state.
[0109] The anionic polymer dispersant preferably has a graft chain, and the graft chain is expected to improve the solubility in various organic solvents.
[0110] The mass average molecular weight of the anionic polymer dispersant is preferably 1000 or more and 100000 or less, more preferably 5000 or more and 70000 or less, and further preferably 10000 or more and 60000 or less. By making the mass average molecular weight of the polymer dispersant 1000 or more, the dispersibility of the inorganic powder in the organic carrier can be improved. When the mass average molecular weight is greater than 100000, the compatibility with the organic carrier and the organic solvent is sometimes reduced, or the particles of the conductive powder, ceramic powder, etc. are agglomerated with each other, or the dispersibility is reduced and the storage stability is reduced.
[0111] Such a polymer dispersant has a carboxyl group or a carboxylic acid anhydride group in the functional group of the main chain. As an anionic polymer dispersant, it is preferred that it further has an oxyethylene group in the graft chain from the viewpoint of adsorption to the inorganic powder.
[0112] The anionic polymer dispersant may contain more than one. That is, multiple polymer dispersants may be contained according to the length of the main chain, the length of the graft chain, the presence or absence of the graft chain, etc. The content of the anionic polymer dispersant in the conductive paste may be appropriately selected in consideration of the viscosity, stickiness, long-term storage properties, etc. of the conductive paste, and may be contained within a range that does not hinder the effect of the present invention.
[0113] For example, the amount of the anionic polymer dispersant added is preferably 0.01 to 5.00 parts by mass, more preferably 0.20 to 2.00 parts by mass, relative to 100 parts by mass of the conductive metal powder content. When the amount of the dispersant added is less than 0.01 parts by mass, there is a tendency that sufficient dispersibility is difficult to obtain. On the other hand, when the amount of the dispersant added is greater than 5.00 parts by mass, the drying property deteriorates, and in addition, the problem of reduced dry film density occurs.
[0114] Such anionic polymer dispersants are known to include copolymers of maleic anhydride and polyoxyalkylenes having an allyl group at the end, copolymers of acrylic acid and polyoxyalkylenes having an allyl group at the end, and copolymers of these compounds and styrene. The structural formulas of such anionic polymer dispersants can be listed as the structural formulas of formula (1) to formula (3) shown in [Chemical 1] to [Chemical 3] below. For example, in formula (1) to formula (3), R is an alkyl group, m is an integer of 2 to 30, and n is an integer of 10 to 30. In addition, R is preferably an alkyl group having 5 to 30 carbon atoms, more preferably an alkyl group having 8 to 25 carbon atoms, and particularly preferably an alkyl group having 10 to 20 carbon atoms.
[0115] [Chemistry 1]
[0116]
[0117] [Chemistry 2]
[0118]
[0119] [Chemistry 3]
[0120]
[0121] The conductive paste of this embodiment may contain a dispersant in addition to an anionic polymer dispersant. For example, as a dispersant (surfactant), an acid dispersant containing a higher fatty acid, phosphoric acid, a polymer surfactant, etc., a cationic dispersant other than an acid dispersant, a nonionic dispersant, an amphoteric surfactant, and a polymer dispersant may be contained.
[0122] The content of the dispersant in the conductive paste can be appropriately selected in consideration of the viscosity, tack, long-term storage properties, etc. of the conductive paste, and can be contained in a range that does not inhibit the effects of the present invention.
[0123] In addition, for any of the anionic polymer dispersants and other dispersants, the mass average molecular weight of the dispersant is preferably 200 to 100,000. More preferably, it is 300 to 30,000. If the mass average molecular weight is less than 200, the dispersibility and storage stability of the particles are sometimes reduced. Usually, the dispersant is adsorbed on the surface of the particles to form an adsorption layer of the dispersant, which imparts electrostatic repulsion and steric repulsion to the particles, thereby obtaining a slurry with excellent dispersibility. However, it is believed that over time, due to the collision of the particles, the particles overcome the repulsive force of the adsorption layer and agglomerate, so the mass average molecular weight is preferably above 200. In addition, if the mass average molecular weight is greater than 100,000, sometimes the compatibility with the organic carrier and the organic solvent is reduced, or the particles are agglomerated with each other, or the dispersibility and storage stability are reduced. In addition, the problem of increased slurry viscosity also arises.
[0124] The total amount of the anionic polymer dispersant and other dispersants added is preferably 0.01 to 5.00 parts by mass, more preferably 0.20 to 2.00 parts by mass, relative to 100 parts by mass of the conductive metal powder. When the dispersant is less than 0.01 parts by mass, it tends to be difficult to obtain sufficient dispersibility. On the other hand, if it is greater than 5.00 parts by mass, the drying property deteriorates, and the problem of reduced dry film density occurs.
[0125] (Method for producing conductive paste)
[0126] The manufacturing method of the conductive paste of the present embodiment is not particularly limited, and a conventionally known method can be used. The conductive paste can be manufactured, for example, by preparing the above-mentioned components and stirring and kneading them using a three-roll mill, a ball mill, a mixer, etc. At this time, if a dispersant is pre-coated on the surface of the conductive powder, the conductive powder will not agglomerate but be fully dispersed, and the dispersant is spread over its surface, making it easy to obtain a uniform conductive paste. In addition, the binder resin can also be dissolved in an organic solvent for the carrier to prepare an organic carrier, and conductive powder, ceramic powder, organic carrier and dispersant are added to the organic solvent for the slurry, and stirred and kneaded with a mixer to prepare a conductive paste.
[0127] In addition, as the organic solvent for the carrier, in order to improve the affinity of the organic carrier, it is preferred to use the same organic solvent as the organic solvent for adjusting the viscosity of the conductive paste. The content of the organic solvent for the carrier is, for example, 5 parts by mass or more and 80 parts by mass or less relative to 100 parts by mass of the conductive powder. In addition, the content of the organic solvent for the carrier is preferably 10% by mass or more and 40% by mass or less relative to the total amount of the conductive paste.
[0128] The surface smoothness of the dry film formed by printing the conductive paste can be evaluated by surface roughness. In addition, the surface roughness of the conductive paste can be measured, for example, by the method described in the examples (using VK-X120 manufactured by KEYENCE, a method for measuring the arithmetic mean height Sa based on the standard of ISO 25178). When the arithmetic mean height Sa is used for evaluation, the surface smoothness of the dry film is preferably 0.10 μm or less.
[0129] [Electronic components, multilayer ceramic capacitors]
[0130] The conductive paste of the present invention can be suitably used in electronic components such as multilayer ceramic capacitors. Multilayer ceramic capacitors have dielectric layers formed using green sheets and internal electrode layers formed using a conductive paste.
[0131] The dielectric ceramic powder contained in the green sheet of the multilayer ceramic capacitor and the ceramic powder contained in the conductive paste are preferably powders of the same composition, for example, barium titanate can be used. The multilayer ceramic capacitor manufactured using the conductive paste of this embodiment can suppress sheet erosion and peeling failure of the green sheet even when the thickness of the green sheet is, for example, 3 μm or less.
[0132] Hereinafter, embodiments of the electronic component and the like of the present invention will be described with reference to the accompanying drawings. In the accompanying drawings, the drawings may be schematically illustrated or scaled appropriately. Figure 1The position and direction of the member are described using an XYZ orthogonal coordinate system shown in FIG. In the XYZ orthogonal coordinate system, the X direction and the Y direction are horizontal directions, and the Z direction is a vertical direction (up and down direction).
[0133] Figure 1 A in and Figure 1 B in FIG. 1 is a perspective view and a side cross-sectional view showing a multilayer ceramic capacitor 1 as an example of the electronic component according to the embodiment. The multilayer ceramic capacitor 1 includes a ceramic multilayer body 10 in which dielectric layers 12 and internal electrode layers 11 are alternately stacked, and external electrodes 20 .
[0134] The following is a description of a method for manufacturing a multilayer ceramic capacitor 1 using the above-mentioned conductive paste. First, a conductive paste is printed on a dielectric layer composed of a green sheet and dried to form a dry film. After a plurality of dielectric layers having the dry film on the upper surface are stacked and pressed to obtain a laminate, the laminate is fired and integrated to produce a ceramic laminate 10 in which internal electrode layers 11 and dielectric layers 12 are alternately stacked. Thereafter, a pair of external electrodes 20 are formed at both ends of the ceramic laminate 10 to manufacture the multilayer ceramic capacitor 1. The following is a more detailed description.
[0135] First, a green sheet as an unfired ceramic sheet using a dielectric material is prepared. Examples of the green sheet include: a dielectric layer slurry obtained by adding an organic binder such as polyvinyl butyral and a solvent such as terpineol to a predetermined ceramic raw material powder such as barium titanate, applied in a sheet form on a support film such as a PET film, and dried to remove the solvent. In addition, the thickness of the dielectric layer formed by the green sheet is not particularly limited, but from the perspective of the miniaturization requirement of the multilayer ceramic capacitor, it is preferably 0.05 μm or more and 3 μm or less.
[0136] Next, a plurality of sheets are prepared in which the conductive paste is printed (applied) on one side of the raw sheet by a known method such as screen printing and dried to form a dry film. In addition, from the viewpoint of the requirement for thinning the internal electrode layer 11, the thickness of the conductive paste (dry film) after printing is preferably set to a thickness of 1 μm or less after drying.
[0137] Next, the green sheet is peeled off from the support film, and the dielectric layers composed of the green sheets and the dry films formed on one side thereof are alternately stacked, and then heated and pressurized to obtain a laminate. In addition, a protective green sheet not coated with conductive paste may be further arranged on both sides of the laminate.
[0138] Next, after the laminate is cut into a predetermined size to form a raw chip, the raw chip is subjected to a debinding treatment and fired in a reducing atmosphere, thereby manufacturing a ceramic laminate 10. In addition, the atmosphere in the debinding treatment is preferably set to air or N2 gas atmosphere. The temperature during the debinding treatment is, for example, above 200°C and below 400°C. In addition, it is preferred that the holding time of the above temperature during the debinding treatment is set to be above 0.5 hours and below 24 hours. In addition, in order to suppress the oxidation of the metal used for the internal electrode layer, the firing is carried out in a reducing atmosphere. In addition, the temperature during the firing of the laminate is, for example, above 1000°C and below 1350°C, and the holding time of the temperature during the firing is, for example, above 0.5 hours and below 8 hours.
[0139] By firing the green chip, the organic binder in the green chip is completely removed, and the raw material powder of the ceramic is fired to form the ceramic dielectric layer 12. In addition, the organic vehicle in the dry film is removed, and the nickel powder or the alloy powder mainly composed of nickel is sintered or melted and integrated to form the internal electrode layer 11, thereby forming a laminated ceramic fired body in which a plurality of dielectric layers 12 and internal electrode layers 11 are alternately stacked. In addition, from the viewpoint of introducing oxygen into the interior of the dielectric layer to improve reliability and suppressing reoxidation of the internal electrode, the laminated ceramic fired body after firing may be subjected to annealing treatment.
[0140] Then, a pair of external electrodes 20 are provided on the manufactured multilayer ceramic fired body, thereby manufacturing the multilayer ceramic capacitor 1. For example, the external electrode 20 includes an external electrode layer 21 and a plating layer 22. The external electrode layer 21 is electrically connected to the internal electrode layer 11. In addition, as a material of the external electrode 20, for example, copper, nickel, or an alloy thereof can be preferably used. In addition, the electronic component is not limited to the multilayer ceramic capacitor, and may also be an electronic component other than the multilayer ceramic capacitor such as a varistor.
[0141] Example
[0142] Hereinafter, the present invention will be described in detail based on Examples and Comparative Examples, but the present invention is not limited to these Examples at all.
[0143] [Materials used]
[0144] (Conductive powder)
[0145] As the conductive powder, Ni powder (number average particle size measured by SEM: 0.2 μm) was used.
[0146] (Ceramic powder)
[0147] As the ceramic powder, barium titanate (BaTiO 3 ; number average particle size based on SEM measurement: 0.05 μm) was used.
[0148] (Binder resin)
[0149] The binder resin was synthesized as follows.
[0150] (Synthesis of Cellulose Compound (1a) Having Vinyl Group)
[0151] Ethyl cellulose ("ETHOCEL STD-100" manufactured by Dow Chemical, number average molecular weight Mn (standard polystyrene conversion value based on GPC): 63420, average number of unetherified hydroxyl groups per glucose ring: 0.48) was prepared and dried.
[0152] 100 parts by mass of the dried ethyl cellulose was dissolved in 900 parts by mass of ethyl acetate to obtain a solution. 0.09 parts by mass of 3-allyloxypropionic acid, which was equivalent to an average of 0.5 vinyl groups introduced per one molecule of ethyl cellulose, 0.10 parts by mass of diisopropylcarbodiimide as a condensing agent, and 0.002 parts by mass of dimethylaminopyridine as a reaction accelerator were added to the obtained solution, and the mixture was stirred at a temperature of 40° C. for 5 hours to react. Thereafter, the ethyl acetate was removed to obtain a cellulose-based compound (1a) having vinyl groups introduced into the ethyl cellulose as a solid.
[0153] A portion of the obtained solid was analyzed by FT-IR and 1H-NMR, and as a result, the formation of an ester bond was confirmed, and it was confirmed that vinyl groups were introduced into ethyl cellulose in an amount equivalent to the molar amount of 3-allyloxypropionic acid charged.
[0154] In the cellulose compound (1a), unreacted ethyl cellulose is mixed with the compound obtained by introducing a vinyl group into ethyl cellulose. However, in the examples, the mixture is referred to as the cellulose compound (1a).
[0155] (Synthesis of polyvinyl butyral compound (1b) having a thiol group)
[0156] Polyvinyl butyral ("BM-SZ" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn (based on standard polystyrene conversion value of GPC): 55000, hydroxyl group content: about 22 mol%) was prepared and dried. 100 parts by mass of the dried polyvinyl butyral was dissolved in 900 parts by mass of ethyl acetate. 0.10 parts by mass of 3-mercaptopropionic acid corresponding to an average introduction amount of 0.5 thiol groups per molecule of polyvinyl butyral, 0.12 parts by mass of diisopropylcarbodiimide as a condensing agent, and 0.003 parts by mass of dimethylaminopyridine as a reaction accelerator were added to the obtained solution, and the mixture was stirred at a temperature of 40°C for 5 hours to react. Thereafter, by removing ethyl acetate, a polyvinyl butyral-based compound (1b) in which a thiol group was introduced into the polyvinyl butyral was obtained as a solid.
[0157] A portion of the obtained solid was analyzed by FT-IR and 1H-NMR, and as a result, the formation of ester bonds was confirmed, and it was confirmed that thiol groups were introduced into polyvinyl butyral in an amount equal to the molar amount of 3-mercaptopropionic acid charged.
[0158] In the polyvinyl butyral compound (1b), unreacted polyvinyl butyral is mixed with the compound having a thiol group introduced into polyvinyl butyral. In the examples, the mixture is referred to as the polyvinyl butyral compound (1b).
[0159] (Synthesis of Polymer Compound 1)
[0160] 5 parts by mass of a cellulose compound (1a) and 4.35 parts by mass of a polyvinyl butyral compound (1b) were dissolved in 60 parts by mass of dihydroterpineol as a solvent, and the solution was transferred to a glass flask reaction container. After nitrogen substitution, 0.1 parts by mass of azobisisobutyronitrile as a free radical generator was added to the solution, and the mixture was reacted at 80°C for 3 hours while stirring to obtain an organic vehicle 1 containing a polymer compound 1. Here, the cellulose compound (1a) and the polyvinyl butyral compound (1b) were the same in molar number. As described above, an average of 0.5 thiol groups were introduced per molecule of polyvinyl butyral, and therefore the molar ratio of sulfur atoms contained in the polymer compound 1 to the total of cellulose and the cellulose compound was 0.5. The organic vehicle 1 contained 13.5% by mass of the polymer compound 1. Here, polymer compound 1 contains a polymer compound in which a cellulose compound (1a) and a polyvinyl butyral compound (1b) are bonded, unreacted ethyl cellulose, and unreacted polyvinyl butyral. However, in the examples, the mixture is referred to as polymer compound 1.
[0161] The generated polymer compound 1 was analyzed by FT-IR and 1H-NMR, and as a result, -S- bonds were confirmed, and the target structure was obtained. Furthermore, the number average molecular weight (Mn: standard polystyrene conversion value based on GPC) of the polymer compound 1 was measured.
[0162] Table 1 shows the characteristics of the cellulose-based compound (1a) and the polyvinyl acetal-based compound (1b) used in the polymer compound 1.
[0163]
[0164] [Example 1]
[0165] A conductive paste is prepared by mixing 47% by mass of Ni powder, 4.7% by mass of ceramic powder, 26.67% by mass of organic carrier 1, 0.4% by mass of anionic polymer dispersant of a polymer polycarboxylic acid having a structural formula represented by the above formula (1) (R is an alkyl group having 5 to 30 carbon atoms and a mass average molecular weight of 40,000), and the balance of 21.23% by mass of an organic solvent (dihydroterpineol), and the total amount is 100% by mass. The surface roughness of the dry film obtained by printing and drying the prepared conductive paste and its close contact with the raw sheet are evaluated as follows. The evaluation results are shown in Tables 2 and 3. Figure 2 .
[0166] [Evaluation method]
[0167] (Dispersibility: Surface roughness of the dry film and adhesion to the green sheet)
[0168] <Surface Roughness>
[0169] The conductive paste produced by screen printing is placed on a 2.54 cm (1 inch) square heat-resistant tempered glass and dried at 120°C for 1 hour in the atmosphere to produce a 20 mm square dry film with a film thickness of 1 to 3 μm. When the dispersibility of the conductive paste is good, the surface of the dry film becomes a smooth film. In the case of poor dispersibility, agglomeration occurs in the conductive paste, the surface of the dry film is rough, and the smoothness of the surface is reduced. Therefore, a laser microscope (VK-X120 manufactured by Keyence Corporation) is used to measure the surface roughness Sa (arithmetic mean height) of the produced dry film based on the standard of ISO 25178. The smaller the value of the surface roughness Sa (arithmetic mean height), the smoother the surface of the dry film.
[0170] Furthermore, the obtained dried film was observed using SEM.
[0171] <Adhesion between dry film and green sheet>
[0172] The printer is adjusted in such a way that the film thickness after printing is 3.6 μm, and the prepared conductive paste is printed on a 2.54 cm (1 inch) square BaTiO3 dielectric green sheet in a 2 cm square pattern. After printing, it is dried at 120°C for 20 minutes to form a dry film of the conductive paste on the surface of the green sheet. Next, the BaTiO3 dielectric green sheet is covered on the dry film of the conductive paste, and the dry film of the conductive paste and the BaTiO3 dielectric green sheet are hot-pressed under an isostatic pressure of 80°C and 98 MPa to produce a laminate. The adhesion between the dry film of the conductive paste and the BaTiO3 dielectric green sheet of the obtained laminate is evaluated by measuring the force of peeling the dry film of the conductive paste and the BaTiO3 dielectric green sheet. The adhesion is measured by a thin film adhesion strength measuring machine (Romulus manufactured by Photo Technica). To specifically describe the process of evaluating the adhesion in the film adhesion strength tester, an aluminum anti-skid spike coated with an epoxy adhesive is vertically bonded to the center of the laminate, and a sample for evaluating the adhesion to which the anti-skid spike is vertically bonded is prepared. The anti-skid spike of the sample is pulled so as to be peeled off from the surface of the laminate, thereby evaluating the adhesion between the dried film of the conductive paste and the BaTiO3 dielectric green sheet. In addition, the evaluation results of the adhesion are shown as the results of relative evaluation with the adhesion strength of Comparative Example 1 described later being 100.
[0173] [Comparative Example 1]
[0174] A conductive paste was prepared and evaluated in the same manner as in Example 1 except that an anionic dispersant of an amide compound of an amino acid and a fatty acid (hereinafter referred to as dispersant B, molecular weight 353) was used. The results are shown in Tables 2 and 3. Figure 2 .
[0175] Table 2
[0176]
[0177] [Evaluation results]
[0178] As shown in Table 2, the surface roughness Sa (arithmetic mean height) of the dry film formed from the conductive paste of Example 1 was 0.06 μm, which was lower than that of Comparative Example 1. Furthermore, as shown in the SEM photographs in Table 2, it was found that the film had less irregularities than that of Comparative Example 1.
[0179] On the other hand, the surface roughness Sa of the dry film formed from the conductive paste of Comparative Example 1 was 0.9 μm, and the surface was rougher than that of Example 1. Moreover, as shown in the SEM photograph of Table 2, the film had larger irregularities than that of Example 1.
[0180] Further, according to Figure 2 It is found that the dry film of Example 1 having excellent surface roughness Sa has better adhesion to the BaTiO 3 dielectric green sheet than the dry film of Comparative Example 1.
[0181] Industrial Applicability
[0182] The conductive paste according to the present embodiment using micronized conductive powder and ceramic powder can provide a conductive paste having a smooth dry film and excellent adhesion. Therefore, it can be particularly suitable for use as a raw material for internal electrodes of multilayer ceramic capacitors that are chip components (electronic components) of electronic devices such as mobile phones and digital devices.
[0183] Description of Reference Numerals
[0184] 1: Multilayer ceramic capacitor;
[0185] 10: Ceramic laminate;
[0186] 11: internal electrode layer;
[0187] 12: dielectric layer;
[0188] 20: external electrode;
[0189] 21: external electrode layer;
[0190] 22: Electroplating layer.
Claims
1. A conductive paste comprising conductive powder, ceramic powder, a dispersant, a binder resin and an organic solvent, wherein: The binder resin includes cellulose, polyvinyl acetal, and a polymer compound in which a cellulose compound and a polyvinyl acetal compound are bonded via sulfur atoms. The molar ratio of the sulfur atoms contained in the polymer compound to the total of the cellulose and the cellulose-based compound is 0.3 to 1.7, The dispersant is an anionic polymer compound.
2. The conductive paste according to claim 1, wherein The dispersant has a carboxyl group or a carboxylic anhydride group.
3. The conductive paste according to claim 1 or 2, wherein: The cellulose-based compound is a cellulose derivative having a thiol group or a vinyl group, The polyvinyl acetal compound is a polyvinyl acetal resin having a thiol group or a vinyl group. When the cellulose derivative has a thiol group, the polyvinyl acetal resin has a vinyl group reactive with the thiol group. When the cellulose derivative has a vinyl group, the polyvinyl acetal resin has a thiol group reactive with the vinyl group.
4. The conductive paste according to claim 3, wherein: The cellulose derivative is ethyl cellulose having a thiol group or a vinyl group, The polyvinyl acetal resin is polyvinyl butyral having a thiol group or a vinyl group.
5. The conductive paste according to claim 1, wherein The cellulose-based compound is a first esterification reaction product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of cellulose. The polyvinyl acetal compound is a second esterification reaction product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of the polyvinyl acetal. When the first esterification reactant has a thiol group, the second esterification reactant has a vinyl group, When the first esterification reactant has a vinyl group, the second esterification reactant has a thiol group, The polymer compound is a thiol-ene reactant of the first esterification reactant and the second esterification reactant.
6. The conductive paste according to claim 5, wherein: The first esterification reaction product is an esterification reaction product formed by dehydration condensation of the carboxyl group of 3-allyloxypropionic acid and the hydroxyl group of ethyl cellulose, The second esterification reaction product is an esterification reaction product formed by dehydration condensation of a carboxyl group of 3-mercaptopropionic acid and a hydroxyl group of polyvinyl butyral.
7. The conductive paste according to claim 1 or 2, wherein: The conductive powder is nickel powder.
8. The conductive paste according to claim 1, wherein The number average particle size of the conductive powder is 0.05 μm or more and 1.0 μm or less.
9. The conductive paste according to claim 1, wherein: The ceramic powder includes barium titanate.
10. The conductive paste according to claim 1, wherein The ceramic powder has a number average particle size of 0.01 μm or more and 0.5 μm or less.
11. The conductive paste according to claim 1, wherein The content of the ceramic powder is 1 mass % or more and 20 mass % or less.
12. The conductive paste according to claim 1, wherein The conductive paste is used for internal electrodes of a multilayer ceramic component.
13. An electronic component, wherein: The electronic component is formed using the conductive paste according to claim 1.
14. A multilayer ceramic capacitor, wherein: The multilayer ceramic capacitor includes at least a laminated body in which a dielectric layer and an internal electrode layer are laminated. The internal electrode layer is formed using the conductive paste according to claim 1 .
Citation Information
Patent Citations
Printer
JP1977024722A
Method of electrolytically oxidizing metallic ions
JP1977099904A